A Critical Role of Peptidylprolyl Isomerase A Pseudogene 22/microRNA-197-3p/Peptidylprolyl Isomerase A Axis in Hepatocellular Carcinoma - Gu, Yuwei; Wang, Chao; Chen, Shengsen; Tang, Jia; Guo, Xiaoxiao; Hu, Wei; Cui, An; Zhang, Dian; Yu, Kangkang; Chen, Mingquan (Frontiers in Genetics, 2021)
The overall burden of HCC worldwide is increasing with the passage of time, while the underlying molecular mechanism of HCC development is still under exploration. Pseudogenes are classified as a special type of long non-coding RNAs (lncRNAs) and they can also regulate gene expression like other types of lncRNAs, playing a vital role in tumorigenesis. Here, we reported that PPIAP22 and its parental gene PPIA were upregulated in HCC and associated with the clinical outcomes of HCC. Further investigation revealed that PPIAP22 might upregulate the expression of PPIA through sponging miR-197-3p, behaving as ceRNA. PPIA could participate in the development of HCC by regulating mRNA metabolic process and tumor immunity based on the functional enrichment analysis. We also found a strong correlation between the expression of PPIA and the immune cell infiltration or the expression of chemokines, especially macrophage, CCL15, and CXCL12. Our findings demonstrate that PPIAP22/ miR-197-3p/ PPIA axis plays a vital role in the progression of HCC by increasing the malignancy of tumor cell and regulating the immune cell infiltration, especially macrophage, through CCL15-CCR1 or CXCL12-CXCR4/CXCR7 pathways.